Water resources management strategy : review on the impacts of Sarawak river barrage on the water quality - Hartini, Binti Mahidin (Universiti Malaysia Sarawak (UNIMAS), 2006)
The Sungai Sarawak Regulation Scheme (SSRS) is the ftrst of its kind in South East Asia and could be one ofthe very few "three in one" infrastructure-combining barrage, lock and bridge. This scheme aimed to improve and maintain the water quality to the quality standard acceptable as a reservoir for water supply for Kuching City and its surrounding areas besides improving the aesthetic value of the river. The effectiveness of SSRS as a tool for water resource management in Kuching area was evalu~ted by comparing the water quality data ofthe pre~barrage era against the post~barrage e~. The data were tested first for nonnality by using One~Sample Kolmogorov Smimov test followed by a descriptive statistics, ANOVA (analysis of variance), Paired Samples T-Test and Trend Analysis. This study concluded that the installation of the barrage across Sarawak River has brought about significant improvement to the dissolved oxygen (00) levels, biochemical oxygen demand (BOD) levels, salinity, turbidity and the bacteria counts, to the section of the river upstream of the barrage. Other water quality parameters such as chemical oxygen demand (COD) and ammoniacal nitrogen (NH3~N) were deteriorated after the installation.